South African social assistance and the 2012 privatised national national payment system: an examination of insecurities and technopolitics in social grant administration and payment - Vally, Natasha Thandiwe (My University, 2016)
In 2012 the South African Social Security Agency (Sassa) contracted a private company, Cash Paymaster Services (CPS), to design a standardised national social assistance payment and registration system. The 2012 system was imagined by the government, the media, and by CPS, as a departure from previous social assistance design. There is a poverty of social assistance scholarship in South Africa which is inquisitive about how grants operate and the ways that we can complicate and reframe our understanding of how associated practices are enacted. I argue that understanding the 2012 system requires attention to the confluence of many factors including technologies (and the associated materiality and infrastructures), state practice (through bureaucracies of social grants), the boundaries of the state, policies and law, privatisation, and waiting. The 2012 system in practice renders claimants and grants insecure with regards to movement: grant money is prone to deductions (the movement of money over which a claimant has no control and potentially an end to movement of money altogether), claimants’ personal information is vulnerable (the unknown and unpredictable movement of data), and there is pressure on claimants’ time (a hemming-in of the free movement of claimants coupled with a lack of choice and possibilities in ‘taking up’ or ‘using’ time). The thesis explores the effects of privatisation, and the roots and revelations of technologies and infrastructures, in the administration and payment of social grants.
A dissertation submitted in fulfillment of the requirements for the degree of Doctor of Philosophy in the Department of Political Studies, University of the Witwatersrand, September 2016
Keywords: Social security--South Africa; Public welfare--South Africa; Electronic funds transfers--South Africa